Analysis of Parental Restrictions on Smartphone Use for Early Childhood - Yuniarni, Desni; Surjaningrum, Endang R.; Dewi, Triana Kesuma (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Negeri Jakarta, 2024)
Smartphone’s use in early childhood is increasing. Parents need to place restrictions on its use. The aim of this research is to analyze restrictions on children's smartphone use. This research is qualitative in form with a case study approach and purposive sampling technique. Participants were 20 parents of children aged 3-6 years in PAUD in the city of Surabaya who filled out the questionnaire online and answered questions directly during the interview. The data collection tool is in the form of a Google form and interview guidelines. Data analysis is in the form of descriptive qualitative. The research results show that all parents have restricted smartphones for their children. Most parents are concerned about the negative impact of smartphone use on children's development and hope that children can limit their use according to the agreement and not be exposed to the negative influence of smartphone use. Therefore, most of the parents allowing their children to use their smartphones only on Saturdays and Sundays for approximately 2 hours. Parents are only allowed to access YouTube Kids application content when accompanied when accessing it. Most parents set limits due to concerns that their children will be exposed to content that is not age appropriate (containing elements of violence and pornography) which will have a negative impact on their development. However, most parents still need time and adaptation to be consistent in doing this. The biggest obstacle is not being able to control the child's emotions, even though it has been conveyed and agreed upon previously. The most common response shown by children is rejection, anger and annoyance, so parents need patience to give them understanding. Consistency in implementing restrictions needs to be done so that children avoid the negative impacts of using smartphones.